Pseudoaneurysms of large arteries associated with AIDS - Piccinato, Carlos Eli; Cherri, Jesualdo; Moriya, Takachi; Souza, Antônio Carlos (São Paulo Medical Journal, 1999)
BACKGROUND: Several vascular complications are known to occur in association with the acquired immunodeficiency syndrome (AIDS) and recent publications have called attention to the development of pseudoaneurysms of large arteries in patients with AIDS. CASE REPORT: We report on 2 patients with AIDS aged 23 and 31 years with pseudoaneurysms of the abdominal aorta and common iliac arteries. After clinical and radiological evaluation by arteriography and computed tomography, the patients were submitted to aneurysmectomy, with the placement of a patch of dacron in the first case and the interposition of a right aorto-iliac and left femoral prosthesis in the second. The second patient developed new aneurysms of the right subclavian and left popliteal arteries 2 months after surgery. Proximal ligation of the right subclavian artery was performed to treat the first aneurysm and resection and interposition of a reversed saphenous vein was carried out to treat the pseudoaneurysm of the popliteal artery. Histopathological examination of the popliteal artery revealed necrotizing arteritis.